Mechanisms of interaction between employers and vocational educational organizations in a situation of uncertainty - Galina N. Fomitskaya; Tatyana S. Bazarova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In a situation of uncertainty, there is a rapid change of priorities, which is reflected both in the requirements for the level of professional training of specialists and in the requests of employers for new specialties. However, the list of specialties and areas of training of workers for the regional economy in the regional system of secondary vocational education is formed on the basis of applications from employers for a five-year perspective, but in a situation of uncertainty, no one can guarantee that in five years graduates of a particular specialty or profession will be in demand in the labor market. To achieve a balance in this problem, it is necessary to develop and implement new mechanisms for interaction between professional educational organizations and employers. The aim of this study is to determine the list of popular vocational education specialties, the description and identification of effective mechanisms of interaction between professional educational organizations and employers that affect the improvement of the quality of specialists training and the indicators of their employment according to their specialty based on the analysis of the indicators of the admission campaign and graduates employment of vocational education system of the Republic of Buryatia.